Factors associated with the intention of students at universitas muhammadiyah surakarta to quit smoking - Nova Desfita Agusetiyani; Tanjung Anitasari Indah Kusumaningrum (Science Midwifery, 2026)
Smoking remains a major public health concern among university students and may lead to various adverse health consequences. Although previous studies have examined smoking cessation intention, limited evidence exists regarding the combined role of the Theory of Planned Behavior, smoking cessation knowledge, and peer support among Indonesian university students. Understanding factors associated with students’ intention to quit smoking is essential for developing effective smoking cessation interventions. This study aimed to identify factors associated with the intention to quit smoking among students at Universitas Muhammadiyah Surakarta. A quantitative study with a cross-sectional design was conducted from January to March 2025 involving 166 active student smokers selected using a total sampling technique. Data were collected through a structured questionnaire based on the Theory of Planned Behavior and analyzed using descriptive statistics, Chi-Square and Fisher’s Exact tests to examine associations between categorical variables, with a significance level of p < 0.05. The results showed that attitude (p < 0.001), knowledge regarding smoking cessation methods (p = 0.001), and peer support (p < 0.001) were significantly associated with smoking cessation intention. Students with positive attitudes, good knowledge, and higher peer support were more likely to intend to quit smoking. In contrast, subjective norms (p = 0.284) and perceived behavioral control (p = 0.107) were not significantly associated with the intention to quit smoking. These findings extend the application of the Theory of Planned Behavior and support universities in strengthening smoking cessation education, peer-based interventions, counseling services, and smoke-free campus policies.